O Processo de Demolição e Desmonte das Irmandades Religiosas na Cidade da Parahyba (1923-1935): “O Caso das Mercês” - Meneses, Marcondes Silva (2014)
This dissertation has as a purpose the process of institutional and physical dismantling of religious brotherhoods that existed in the City of Parahyba (João Pessoa/PB nowadays) in the beginning of XX century. The churches of the brotherhoods of Nossa Senhora do Rosário do Preto, Nossa Senhora das Mercês and Nossa Senhora Mãe dos Homens had been built between the late seventeenth century and the eighteenth century when they had an important role in assisting their members and their churches were landmarks in the urban situation. But in 1923 and 1935 they were demolished pointing local historiography to justify this fact as part of the works of urbanization and modernization of the city. However, this present research comes to add new data of this history version which allows lifting up some hypotheses about a convergence of Church and State interests that culminated with the disappearance of these brotherhoods in the city of Parahyba. Documents listed in the historical and ecclesiastical archives have revealed that the church had a clergy reorganization proposal in Parahyba, involving the dismantling of institutional lay’s brotherhoods at the same time the government proposed modernizing interventions that also provided for the demolition of temples belonging to the same brotherhoods. We deepen this issue by analyzing the most emblematic of these processes of dismantling and demolition, which was reported by the local press under the title "the case of Mercês" which gained evidence by the clash between the agents involved: the diocese, the brotherhoods and the government.